The Necessity of Lymph Node Dissection Between Sternocleidomastoid and Sternohyoid Muscles in pN1b Papillary Thyroid Carcinoma - Zhai, Yuanpeng; Ruan, Litao (Frontiers in Endocrinology, 2022)
Background: This study aimed to evaluate the association between clinicopathologic variables and metastasis of the lymph node (LN) between the sternocleidomastoid and sternohyoid muscles (LNSS) to clarify the necessity of LNSS dissection in papillary thyroid carcinomas (PTCs). Methods: A total of 219 patients undergoing unilateral or bilateral neck dissection for PTCs were prospectively enrolled. The associations between clinicopathologic variables and LNSS metastasis were evaluated by univariate and multivariate analyses. Results: LNSS was present in 108 (40.1%) neck dissection samples and in 76 (34.7%) patients. Positive LNSS occurred in 40/269 (14.9%) neck dissection samples and in 20/219 (9.1%) patients. Univariate analysis showed that tumor stage, number of positive nodes in level Ⅲ, and number of positive nodes in level Ⅳ were related to LNSS metastasis. Multivariate analysis confirmed that T3/4 stage tumors and >2 positive LNs in level Ⅳ independently increased the risk of LNSS metastasis. Conclusions: The low rate of LNSS metastasis would deem routine dissection unnecessary; however, LNSS would require excision if advanced stage tumors or level IV LN metastasis were present.